Pengembangan Media Pembelajaran Matematika Berbasis Android Pada Materi Komposisi dan Dekomposisi di Kelas IV B SDN Tebet Timur 07 Jakarta - Az-Zahra, Lamda Diva; Satriyani, Febrianti Yuli (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to develop an Android-based mathematics learning media on the topic of composition and decomposition for Frade IV students at SDN Tebet Timur 07 Jakarta, which is theoretically valid, highly feasible, and implementable, thus effective in achieving learning objectives. The research was conducted using the ADDIE development model (Analysis, Design, Development, Implementation, And Evaluation). The media validation result indicate a high level oh feasibility: 84,4% from the design expert (categorized as very feasible), 98,5% from the IT expert (very feasible), and 100% from the language expert (very feasible). All four expert provided scores within the 81-100% range, which, based on table 3.10, is categorized as “very feasible” for use. The effectiveness level of the Android-based mathematics learning media on the topic of composition and decomposition achieved an average test score of 83.3 in the small-scale trial. This increased to a score of 90 in the large-scale trial, showing an improvement of 6.7 points. Furthermore, the student response questionnaire results received a "very good" rating in terms of reaction and usage, with a score of 92.1% in the small-scale trial. This further increased to 92.8% in the large-scale trial, still in the "very good" category. The student response score thus increased by 0.7 points between the small and large-scale trials, indicating that the learning media was rated as "very good" in terms of implementation. Additionally, the teacher response showed a "very practical" rating with a score of 96.9% based on the teacher response questionnaire, indicating that the learning media is highly practical in terms of usability. Therefore, it can be concluded that the Android-based mathematics learning media on the topic of composition and decomposition for Grade IV B students at SDN Tebet Timur 07 Jakarta has proven to meet high eligibility standards for use in the learning process and has successfully improved student learning outcomes